Minister of Education and Culture Regulation Number 65 of 2013 concerning Elementary and Secondary Education Process Standards - Emha Dzia’ul Haq (Journal of Contemporary Gender and Child Studies, 2024)
Process standards are criteria regarding the implementation of learning in elementary and secondary education units to achieve graduate competencies. The legal basis governing educational process standards is contained in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 65 of 2013. In the implementation of process standards, it can be said that it has been carried out well, by professional teachers. Its implementation can run effectively, efficiently in accordance with the planning that has been set for achieving graduate competency standards that meet the graduation standard requirements. The obstacles or constraints include: a learning system that is less efficient and effective, inadequate facilities and infrastructure and the role of teachers in teaching who are less competent. The most frequent impact that appears and occurs in process standards is a very low learning system. With very incompetent teacher quality.